Eurasian otter (lutra lutra) in central Italy : non-invasive methods to assess status and conservation of a threatened population - Lerone, Laura (Università degli studi Roma Tre, 2013)
The Eurasian otter (Lutra lutra) is a semi-aquatic mustelid of high conservation concern in Europe and especially in Italy where is still considered Critically Endangered (CR). During the last Century, the species suffered a hard decline all over its range and it went extinct in northern and central Italy until the beginning of XXIst Century, when a remnant population was found in central Italy (Molise region). The Italian otter population is geographically and genetically isolated from the other European populations and, to date, consists of two major nuclei in south and south-central peninsula. Despite the high risk of extinction, data on the biology and ecology of the Italian otter population are scanty and fragmented. The results of this PhD research project provided new insights on population density, scent-marking behaviour and individual spatial distribution. We applied non-invasive methods, in particular trapping techniques and non-invasive genetic sampling (NGS) to gather data, considering the Eurasian otters high conservation concern, elusiveness and rarity. Both camera trapping and NGS, commonly used in wildlife research, presented some specific issues when applied to otters. Detection problems arose when trying to record otters with camera traps at marking sites along the watercourses. We hypothesized that the temperature difference between the otter body and the environment was too low to be detected by standard infrared sensors (PIR) so we designed and tested a pressure trigger to activate cameras. The device resulted effective in detecting animals and recording both photos and videos of wild otters at marking sites. Data obtained by remote cameras confirmed the nocturnal habits of the species in the study area. Non-invasive genetics is a powerful tool in wildlife research and monitoring, nevertheless otter DNA obtained from scats (spraints) and anal secretions (jellies) is exposed to very quick degradation processes, and success rate in DNA amplification is much lower than in other carnivores. We collected 235 samples along the river Sangro and its main tributaries (central Italy). Using two sets of microsatellite loci (Set 1: six Lut loci and Set 2: seven OT loci) we investigated the influence of sample freshness and type on genotyping success. We also tested efficacy of different DNA extraction kits and storage buffer solutions in order to optimize future analyses. We finally compared amplification success rate, allelic dropout (ADO) and false alleles (FA) rates in the two STR loci sets. Genetic data permitted us to identify at least 14 otters in the study area, 4 females, 8 males and two individuals of uncertain molecular sexing. Geographical coordinates of individual genetic captures were used to infer the spatial distribution and social structure along the river Sangro. Genotypes were finally analysed to highlight relatedness. We assessed the presence of four familiar groups with large spatial overlap among individuals. This aspect have to be further investigated because may suggests a more complex social system.